A Literature Review on the Imidazole - Shallal, Muhammed Abdel Hasan (American International Journal of Multidisciplinary Scientific Research, 2019)
This review  gives  some  information  about  imidazole  ring  as a ( ligand , complex , antimicrobial , antimalarial , anticancer , uses , applications , linked   with  active  groups  such  as  Schiff  base , azo  group , ..).